Anisotropic Fluid Phase Formed by Ionic Liquid-Crystalline Materials with Ammonium Ions - Tomitaka, Shiori; Wu, Jinzhi; Nata, Masanori; Ujiie, Seiji (Journal of Applied Solution Chemistry and Modeling, 2017)
Ionic liquid-crystalline materials (ILCMs) with ammonium ions were synthesized. Their thermal and orientational properties were studied by polarizing microscopy, differential scanning calorimetry, and X-ray diffraction (XRD). The ILCMs formed the smectic A phase on heating and cooling. A focal conic fan texture was observed in the phase. In addition, the ILCMs spontaneously formed a perpendicular alignment in the smectic A phase. The XRD patterns of the ILCMs consisted of sharp reflections in the small-angle region and broad band in the wide-angle region in the smectic A phase.